Dietary strategies for optimizing omega-3 fatty acid intake: a nutrient database-based evaluation in Taiwan - Lu, Shih-An; Lee, I-Ta; Tan, Chui Xuan; Wang, Shang-Ta; Praveen, Keerthi; Lee, Wei-Ju (Frontiers in Nutrition, 2025)
IntroductionOmega-3 fatty acid consumption is increasingly important for overall health.MethodsThis study assessed the effectiveness of different omega-3 sources, including oils, nuts, seeds, and aquatic foods, in a particular cultural setting using information from the Taiwan Food and Drug Administration Food Nutrient Database.ResultsAmong edible oils, 22.7% contained omega-3 levels exceeding 0.2 g/g, with flaxseed oil requiring only 2–3 g/day to meet α-linolenic acid (ALA) recommendations of the National Institutes of Health (NIH). Flaxseed, rapeseed, walnut, canola, and soybean oils can meet ALA intake recommendations, with flaxseed and chia seeds being the most efficient sources, requiring only 5–7 g/day. Mackerel and Pacific saury were the most efficient eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) sources, requiring only 6 g/day, whereas 81% of crustaceans and 73.3% of mollusks contained <0.01 g/g of omega-3, necessitating much higher intake. Integration with the Food Consumption Database showed that while the 95th percentile and mean ALA intakes exceeded NIH recommendations, median levels fell below, indicating a deficiency risk for over half the population. EPA and DHA intake were generally inadequate, particularly among girls aged 16–18 and children under 3, except in adults and the elderly.DiscussionThese findings underscore the need to promote public awareness of potential omega-3 deficiency.